2002
DOI: 10.1128/jcm.40.9.3523-3525.2002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Blood-Borne Infectious Diseases in Blood Donors in Ghana

Abstract: Transfusion-transmissible infections among 808 blood donors in Ghana were investigated in 1999. Antibody seroprevalences of 3.8, 0.7, 8.4, and 13.5%, respectively, for human immunodeficiency virus, human T-cell lymphotrophic virus type 1, hepatitis C virus (HCV), and Treponema pallidum were obtained. The seroprevalence of HCV infection was confirmed to be 0.9% after supplementary testing, and the transfusion risk potential of these pathogens was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
71
10

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 12 publications
(13 reference statements)
22
71
10
Order By: Relevance
“…This result is consistent with HCV seroprevalence ranging between 0.9 and 6.7% reported from previous studies in Ghana and neighboring West African countries (1,4,10,19,48). The differences observed are probably related to the populations studied (blood donors, children, pregnant women, general population) and the testing algorithm used (one or more EIA screening assays followed or not by a confirmatory assay).…”
Section: Discussionsupporting
confidence: 79%
“…This result is consistent with HCV seroprevalence ranging between 0.9 and 6.7% reported from previous studies in Ghana and neighboring West African countries (1,4,10,19,48). The differences observed are probably related to the populations studied (blood donors, children, pregnant women, general population) and the testing algorithm used (one or more EIA screening assays followed or not by a confirmatory assay).…”
Section: Discussionsupporting
confidence: 79%
“…24 The overall prevalence of anti-HTLV-1 antibodies among HIV positive patients found ............................................................................................................................................. in this study is markedly higher than previously reported in African blood donors. 9,25,26 This would be consistent with those subjects with HIV also being at increased behavioral risk for acquiring HTLV-1 infection as both viruses have the same routes of transmission. However, it could equally be consistent with widespread epidemics of HIV and HTLV-1 running in parallel but with different transmissibility parameters.…”
Section: Discussionsupporting
confidence: 64%
“…However, recently we reported HTLV-I seroprevalence rates of 4?2 and 11?29 % among blood donors and human immunodeficiency virus (HIV)/AIDS patients in Ghana, respectively (Adjei et al, 2003a, b). Two earlier studies among blood donors presenting to blood banks in the late 1990s in Ghana reported an HTLV-I seroprevalence of 0?5-0?7 % (Sarkodie et al, 2001;Ampofo et al, 2002). In a much earlier related study, Lal et al (1994) reported the seroprevalence of HTLV-I among urban and rural dwellers in southern Ghana to be 1-2 %.…”
Section: Introductionmentioning
confidence: 96%